Komodifikasi dan Budaya Partisipatif Media Sosial dalam Komunikasi Pemasaran Produk Skincare di Aplikasi TikTok - Hernawo, Toto (CommLine, 2025)
This study aims to analyze the marketing communication strategies of skincare products on TikTok using the media commodification theory and participatory social media culture. In the digital era, TikTok is not only a medium for entertainment but also a strategic channel for building consumer engagement through creative content. This study used a qualitative content analysis method on five viral skincare promotional campaigns on TikTok. The analysis results show that the commodification process occurs at the content, audience, and platform levels, while participatory social media culture encourages active audience involvement in the process of disseminating promotional messages. This study concludes that marketing communication on social media has undergone a transformation, from being one-way to collaborative and community-based.